Development of Multiple Crosslinked Polymers and Its Application in Synthetic-Based Drilling Fluids - Jun Yang; Tengfei Dong; Jingtian Yi; Guancheng Jiang (Gels, 2024)
This study addresses the performance challenges of Synthetic-Based Drilling Fluids (SBDF) in deep wells and high-temperature environments by engineering a novel multiple hydrogen-bonded crosslinked polymer, MBAH/nano-SiO2. Synthesized using methyl methacrylate (MMA), butyl methacrylate (BMA), acrylic acid (AA), N-hydroxyethyl acrylamide (HEAA), and nano-silica (nano-SiO2), the polymer improved crosslinking density, thermal properties, particle size distribution, and colloidal stability. The development of a ‘weak gel’ structure in W/O emulsions improved rheology and electrical stability (ES), with ES values reaching up to 775 V after aging at 180 °C. Moreover, the polymer’s amphiphilic structure and the synergistic effect of nano-SiO2 increased emulsion film thickness and strength, further augmenting stability. The high-temperature and high-pressure filtration loss of SBDF was considerably reduced to 7.6 mL, benefiting well wall stability and reservoir damage control. This study provides crucial insights into optimizing multiple hydrogen-bonded crosslinked strategies and polymers in SBDF applications.